2014
DOI: 10.1159/000360839
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Aspects of Lynch Syndrome and Familial Adenomatous Polyposis

Abstract: Background: The most frequent hereditary colorectal cancer (CRC) syndromes are Lynch syndrome and familial adenomatous polyposis (FAP), accounting for approximately 5% of the CRC burden. Both are characterized by an autosomal dominant mode of transmission and require an individualized approach of intensified screening and prophylactic surgery. Methods: In this review, we provide an overview of the literature regarding gene- and gender-specific aspects of Lynch syndrome and FAP. Based upon available data, a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Using the tumour-specific LR s to estimate variant TCLRs , the proportion of predicted VUS based on MVP+ TCLR pred model increased (online supplementary figure S5). Interestingly, we also observed higher MSI/IHC LRs in patients with younger diagnosis age (online supplementary table S8), which is consistent with previously reported higher cancer risks in patients with early-onset cancer,38 39 although the application of TCLR stratified by diagnosis age yielded a high AUC and predicted clinical significance for 62.7% of VUS, similar to results among all patients (online supplementary figure S5 and S6). Similarly, high AUCs and increased proportion of reclassified VUS based on MVP+ TCLR pred model were observed using gene-specific LRs (online supplementary figure S5 and S7).…”
Section: Discussionsupporting
confidence: 91%
“…Using the tumour-specific LR s to estimate variant TCLRs , the proportion of predicted VUS based on MVP+ TCLR pred model increased (online supplementary figure S5). Interestingly, we also observed higher MSI/IHC LRs in patients with younger diagnosis age (online supplementary table S8), which is consistent with previously reported higher cancer risks in patients with early-onset cancer,38 39 although the application of TCLR stratified by diagnosis age yielded a high AUC and predicted clinical significance for 62.7% of VUS, similar to results among all patients (online supplementary figure S5 and S6). Similarly, high AUCs and increased proportion of reclassified VUS based on MVP+ TCLR pred model were observed using gene-specific LRs (online supplementary figure S5 and S7).…”
Section: Discussionsupporting
confidence: 91%
“…Combined, these syndromes account for only 5% of all CRC cases. Lynch syndrome/hereditary non-polyposis colorectal cancer (HPNCC) and familial adenomatous polyposis (FAP), have been reported to present a significant gender gap in associated CRC risk ( 245 ). With Lynch syndrome/HPNCC females have a cumulative CRC lifetime risk of 30%, whereas men have a risk of 54%.…”
Section: Genetic Sexual Differentiation In Crcmentioning
confidence: 99%
“…As mentioned above, certain hereditary syndromes, such as Lynch syndrome and FAP, are associated with higher risk of developing CRC but that risk displays a significant gender gap. Lynch syndrome/HPNCC females have a cumulative CRC lifetime risk of 30%, whereas men have a risk of 54% ( 245 ). Based on this evidence, it is timely to suggest not only gene but sex-based adapted screening and surgical recommendations for both syndromes.…”
Section: Gender Gap In Crcmentioning
confidence: 99%
“…HNPCC mostly affects the proximal part of the colon in 70% of cases and in the remaining 30%, its localization is sporadic. According to our observation, HNPCC occurring in younger patients (age, <45 years) tends to involve the proximal areas and sporadic areas in older patients (age >65 years) ( 11 , 12 ). The average age of Lynch syndrome-associated CRC manifestation is 45 years, which is~20 years lower than in the sporadic counterpart ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 72%
“…According to our observation, HNPCC occurring in younger patients (age, <45 years) tends to involve the proximal areas and sporadic areas in older patients (age >65 years) ( 11 , 12 ). The average age of Lynch syndrome-associated CRC manifestation is 45 years, which is~20 years lower than in the sporadic counterpart ( 11 , 12 ). A study by Lindor et al ( 13 ) reported that >40% of HNPCCs were located on the proximal areas rather than having a sporadic location.…”
Section: Introductionmentioning
confidence: 72%